Determinants of Sleepiness at Wheel and Missing Accidents in Patients With Obstructive Sleep Apnea - Fanfulla, Francesco; Pinna, Gian Domenico; Marrone, Oreste; D’Artavilla Lupo, Nadia; Arcovio, Simona; Bonsignore, Maria R.; Morrone, Elisa (Frontiers in Neuroscience, 2021)
Study Objectives Motor-vehicle crashes are frequent in untreated OSA patients but there is still uncertainty on prevalence as well as physiological or clinical determinants of sleepiness at the wheel (SW) in OSA patients. We assessed determinants of SW or sleepiness related near-miss car accident (NMA) in a group of non-professional drivers with OSA. Methods A 237 consecutive, treatment-naïve PSG-diagnosed OSA patients (161 males, 53.1 ± 12.6 years) were enrolled. Self-reported SW was assessed by positive answer to the question, “Have you had episodes of falling asleep while driving or episodes of drowsiness at wheel that could interfere with your driving skill in the last year?” Occurrence of NMA in the last 3 years was also individually recorded. Habitual self-reported average sleep time was collected. Results SW was found in 41.3% of patients but one-quarter of patients with SW did not report excessive daytime sleepiness. Predictors of SW were the following subjective factors: Epworth sleepiness scale score (ESS-OR 1.26; IC 1.1–1.4; p < 0.0001), depressive symptoms (BDI-OR 1.2; IC 1.06–1.18; p < 0.0001) and level of risk exposure (annual mileage-OR 1.9; IC 1.15–3.1; p = 0.007). NMAs were reported by 9.7% of patients, but more frequently by SW+ than SW– (22.4% vs. 0.7%; χ2 31, p < 0.0001). The occurrence of NMAs was significantly associated to ESS, BDI, habitual sleep duration and ODI (R2 = 0.41). Conclusion SW is not predicted by severity of OSA. Evaluation of risk exposure, assessment of depressive symptoms, and reported NMA should be included in the clinical evaluation, particularly in patients with reduced habitual sleep time and severe nocturnal hypoxia.